2007
DOI: 10.1007/bf02877767
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin sensitivity on SHBG levels in premenopausal versus postmenopausal obese women

Abstract: This study was performed to evaluate the impact of insulin sensitivity on sex hormone-binding globulin (SHBG) and sex steroids in premenopausal and postmenopausal euthyroid obese women. A total of 227 women were eligible for this study. All were euthyroid, obese, and overweight; ages ranged from 25 to 69 years. Women were divided into premenopausal (n=151) and postmenopausal (n=76) groups. SHBG, sex steroids, thyrotropin, fasting and postprandial glucose, lipid profile, uric acid, serum insulin, and blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Given the association between lower SHBG and insulin resistance in both men and women [1, 2, 4, 7, 9, 10] and the relation between low SHBG and higher plasma glucose [14], our findings are further evidence for the link between socioeconomic disadvantage and future risk of impaired glucose regulation.…”
Section: Discussionmentioning
confidence: 59%
“…Given the association between lower SHBG and insulin resistance in both men and women [1, 2, 4, 7, 9, 10] and the relation between low SHBG and higher plasma glucose [14], our findings are further evidence for the link between socioeconomic disadvantage and future risk of impaired glucose regulation.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, it could be argued that SHBG level can be correlated with insulin resistance for postmenopausal women. [28] The major difÞ culty with our study is that values of the SHBG concentrations were scattered. The mean value was 64.2 nmol/L with SD of 50.3, therefore we used median SHBG concentration to show the signiÞ cance of the work.…”
Section: Discussionmentioning
confidence: 86%
“…In humans, there tends to be an inverse relationship between plasma insulin level and SHBG concentration (Akin et al, 2009; Preziosi et al, 1993), which implicates severity of insulin resistance in determining SHBG levels. Insulin resistance and SHBG concentration have been examined in a number of clinical studies, and it has been consistently shown that low SHBG levels correlate with higher HOMA-IR scores (Akin et al, 2007; Akin et al, 2009; Davis et al, 2012b; Kalish et al, 2003; Li et al, 2010; Yasui et al, 2007). This relationship appears independent of BMI (Davis et al, 2012b), but may be mediated by abdominal obesity (Akin et al, 2009).…”
Section: Estrogen Regulation Of Whole-body Metabolismmentioning
confidence: 99%
“…The Study of Women’s Health Across the Nation found that overall, there were no significant longitudinal changes in SHBG across the menopause transition, and any small decreases in SHBG levels were driven by changes in adiposity (Wildman et al, 2012). Interestingly, however, some studies have found that the inverse association between HOMA-IR and SHBG levels is only seen in postmenopausal, not premenopausal, women (Akin et al, 2007; Akin et al, 2009; Davis et al, 2012b). After menopause, type of hormone therapy can also affect SHBG levels; based on a number of small clinical studies, oral E 2 therapy increases plasma SHBG levels, whereas transdermal therapy has no effect (Selby et al, 1989; Taskinen et al, 1996; Vehkavaara et al, 2000) (reviewed in (Goodman, 2012)).…”
Section: Estrogen Regulation Of Whole-body Metabolismmentioning
confidence: 99%